Natural products regulate mitochondrial function in cognitive dysfunction—A scoping review - Tuo, Jinmei; Peng, Yan; Linghu, Yushuang; Tao, Ming; Huang, Shiming; Xu, Zucai (Frontiers in Pharmacology, 2023)
Medicines from natural products can not only treat neurodegenerative diseases but also improve the cognitive dysfunction caused by treatments with western medicines. Therefore, the purpose of the present study was to review the literature related to the regulation of mitochondrial participation in cognitive function by natural products. In this study, we focused on English articles in PubMed, Web of Science, and Google Scholar, from October 15, 2017, to October 15, 2022. Fourteen studies that followed the inclusion criteria were integrated, analyzed, and summarized. Several studies have shown that natural products can improve or reduce cognitive dysfunction by ameliorating mitochondrial dysfunction. These results suggest that natural products may serve as new therapeutic targets for neurodegenerative diseases.